Today's Technician: Automotive Brake Systems, Classroom and Shop Manual Pre-Pack, 7th Edition - Ken Pickerill (Cengage Learning, 2018)
This comprehensive resource includes everything you need to understand, diagnose, and repair today's brake systems with confidence--and prepare for ASE certification and career success as an automotive technician. In addition to thorough coverage, accurate and up-to-date details, and abundant illustrations, TODAY'S TECHNICIAN: AUTOMOTIVE BRAKE SYSTEMS, CLASSROOM AND SHOP MANUAL PRE-PACK, Seventh Edition, offers a uniquely convenient two-volume approach. The first volume is a Classroom Manual covering the theory and application of the total brake system, subsystem, and components. Volume two is a Shop Manual that explores real-world symptoms, diagnostics, and repairs, and is ideal for standalone use as a reference on the job. In addition to aligning with the ASE Education Foundation 2017 accreditation model, the Seventh Edition features job sheets correlated to specific MLR, AST and MAST tasks, and extensive information on new and emerging technology and techniques--including hybrid vehicles, brake by wire, and electric brakes.